RETRACTED: Prevalence of coronary artery disease and its risk factors in Majmaah City, Kingdom of Saudi Arabia - Albar, Haitham M.; Alahmdi, Riyadh Ahmed; Almedimigh, Abdulmalik A.; Shaik, Riyaz Ahmed; Ahmad, Mohammad Shakil; Almutairi, Abdulaziz Badar; Alghuyaythat, Waleed Khalid Z.; Alaoufi, Shouq Yaseen; Aloyari, Worud Omar; Alanazi, Rand Muslat S. (Frontiers in Cardiovascular Medicine, 2022)
Objective This study was carried out with an aim to outline the prevalence of coronary artery diseases, its risk of one region of the Saudi Arabia. Methods A retrospective observational study conducted across five secondary medical centers located in the city of Majmaah. Hospital medical records and ministry of health records were screened over a 6-month period for data on patients admitted for Coronary artery disease (CAD). Data collected included sociodemographic characteristics, medical profile, and laboratory findings. Results A total of 327 participants were included in this study with a median age of 64 and the majority being male participants (59.8%). The majority were married, held a primary school degree and earned a salary for living. A large number (82.9%) were hypertensive and diabetic (66.7%) and one-fourth had a previous MI (25.1%). A large number (73.7%) had heart failure with a mean ejection fraction of 44% (SD = 13). The causes of heart failure were mainly ischemic (56.3%) and hypertensive (28.1%). Readmission rates at 30 and 90 days then at 6 and 12 months were 22, 53.8, 68.8, and 75.8%, respectively. The mortality rates at the same time intervals were 5.5, 8.9, 14.1, and 22.9%, respectively. Predictors of readmission are age, CCI, and NYHA class. Conclusion Coronary artery disease is the leading cause of heart failure. End stage CAD can have similar results in terms of readmission and mortality as heart failure. Future research should target patients in different stages of the condition and monitor their comorbidities which may impact the study findings.